Historical and epistemological bases of LGBTQIA+ Museology (Cadernos de Sociomuseologia, 2025)
Abstract: introductory part of the undergraduate discipline LGBTQIA+ Museology, offered mainly in Museology undergraduate courses in Brazil and mini-courses, this text aims to identify the historical and epistemological bases of the LGBTQIA+ Museology category. To this end, it presents the influences coming from museological thinking, Democracy and academic studies on gender and sexuality, such as Queer Theory.Keywords: LGBTQIA+ Museology; Museums; Democracy; LGBTQIA+ Movement; Queer Theory.